Final Answer:
The inverse of the function h(x) = 5/2x + 4 is h^(-1)(x) = (2x - 8) / 5.
Step-by-step explanation:
To find the inverse of h(x), we need to swap the positions of x and h(x) and solve for x. Here's how we can do it:
Replace h(x) with y:
y = 5/2x + 4
Swap x and y:
x = 5/2y + 4
Isolate x:
Subtract 4 from both sides: x - 4 = 5/2y
Multiply both sides by 2: 2(x - 4) = 5y
Divide both sides by 5: (2x - 8) / 5 = y
Replace y back with h(x):
h^(-1)(x) = (2x - 8) / 5
Therefore, the inverse of h(x) is h^(-1)(x) = (2x - 8) / 5.